Future-proofing world trade in technology: Turning the WTO IT Agreement (ITA) into the International Digital Economy Agreement (IDEA) - Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2011)
Despite being an agreement designed for the fastest developing sectors, the signatories of the Information Technology Agreement (ITA) in the World Trade Organization (WTO) have so far failed to re-negotiate the coverage of the ITA (concluded in 1996) due to a longstanding dispute amongst its members. Since then, a new digital economy has been established and several products have been developed or merged with others, become obsolete, or turned into services. Supply chains in the ICT sector have become fragmented, and gains from increases in productivity and welfare benefits have benefitted the developing economies. The WTO framework is struggling to keep up with these new challenges but the lack of progress risks turning the ITA into an obsolete agreement at the same time as the deadlock contributes to the proliferation of bilateral free trade agreements (FTAs). Nevertheless, FTAs cannot replace a "critical mass" agreement with near-full participation under the auspices of the WTO - an agreement that would be very costly for WTO members to stand outside and also make the complex rules of origin obsolete for the complex ICT products. This working paper proposes a "future-proofing" of the ITA by suggesting the creation of an International Digital Economy Agreement (IDEA) that could expand the current agreement by 40% compared to today's levels: Expansion of the product coverage based on two-tier criteria: inclusion of all products that register, store, process, communicate or render information; and that use digital technology. Many tariff line commitments should be made on category (four-digit) level instead of product-by-product basis. Future additions in the categories would then be included automatically and could only be excluded through negotiations. Establishment of a new system of mutual recognition on product-by-product basis, complemented by a general acceptance of supplier declaration of conformity (SDoC). Encompassment of services trade in computer and related services (CRS, where critical mass should already exist) and telecommunication services. New technologies and developments, like cloud computing, managed services or increasing number of products that depend on online access call for revision of existing protocols. The sector strives on borderless use of competence, and mode 4 is also a key interest of developing economies. Therefore there is a strong political and economic rationale for including intra-corporate transfers and quotas on temporary movement of workers (mode 4) replacing economic needs tests (ENTs) and other barriers. Finally, the membership of the International Digital Economy Agreement could be expanded. There are six priority economies for membership - Argentina, Brazil, Chile, Mexico, Russian Federation and South Africa. These account for 6.7 % of ICT trade but they are also key players in the Doha round, suggesting that the plurilateral agreement could soon develop the same complications as multilateral negotiations.
Keywords: F13; F14; F22; F23; F53; O14; O24; 330; World Trade Organization; Information Technology Agreement; trade in information technology; customs classification; dispute settlement; trade in services